The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1519-6984.274971
|View full text |Cite
|
Sign up to set email alerts
|

Opiliofauna (ARACHNIDA: OPILIONES) of the Atlantic Forest in the state of Paraná, Brazil

L. G. T. Rubim,
T. H. R. Pádua,
A. S. B. Souza
et al.

Abstract: Opiliones are arachnids that provide different services in terrestrial ecosystems, especially in tropical forests, which justifies inventory studies to better understand the occurrence and distribution of these arthropods in Brazil, since little is known about the harvestmen fauna in Conservation Units such as in the state of Paraná. In this context, the objective of the present study was to survey the harvestmen fauna at the Iguaçu National Park (PARNA) and in the Bela Vista Biological Refuge (BVBR), from Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The harvestmen richness found in our study is significant when compared to other studies conducted in areas of Atlantic Forest within the interior of the country, where seasonal semi-deciduous forest predominates (Oliveira Filho 2006). In these regions, the number of species varies from seven to 17 per locality (Ferreira et al 2019(Ferreira et al , 2020Gomes et al 2021;Rubim et al 2023). The explanation for the high richness in this study may result from two associated factors: first, the high humidity in the high-altitude forest within the Serra da Mantiqueira, which reaches over 1600 meters (Melo and Salino 2007), decreasing the risk of death due to body dehydration (Curtis and Machado 2007); second, the degree of conservation of the higher fragments in the municipality, as shown in different studies (Stefani-Santos et al 2021;Vieira et al 2022), which increases the richness and abundance of harvestmen, as demonstrated in the studies of Bragagnolo et al (2007) (Giltay, 1928).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The harvestmen richness found in our study is significant when compared to other studies conducted in areas of Atlantic Forest within the interior of the country, where seasonal semi-deciduous forest predominates (Oliveira Filho 2006). In these regions, the number of species varies from seven to 17 per locality (Ferreira et al 2019(Ferreira et al , 2020Gomes et al 2021;Rubim et al 2023). The explanation for the high richness in this study may result from two associated factors: first, the high humidity in the high-altitude forest within the Serra da Mantiqueira, which reaches over 1600 meters (Melo and Salino 2007), decreasing the risk of death due to body dehydration (Curtis and Machado 2007); second, the degree of conservation of the higher fragments in the municipality, as shown in different studies (Stefani-Santos et al 2021;Vieira et al 2022), which increases the richness and abundance of harvestmen, as demonstrated in the studies of Bragagnolo et al (2007) (Giltay, 1928).…”
Section: Discussionmentioning
confidence: 99%
“…Harvestmen (Arachnida) have over a thousand species recorded in Brazil, with around 600 occurring in the Atlantic Forest (Kury 2023), making the Atlantic Forest the world's richest area for the occurrence of harvestmen. However, despite the increasing number of inventory studies in this biome (for example, Bragagnolo and Pinto-da-Rocha 2003;Resende et al 2012a, b;Nogueira et al 2019;Ferreira et al 2019Ferreira et al , 2020Costa et al 2020;Rubim et al 2023), there are locations, including Conservation Units (UC), that lack information about the composition of these arachnid communities, such as the Fernão Dias Environmental Protection Area (Fernão Dias EPA, from now on) in the Serra da Mantiqueira, Minas Gerais.…”
Section: Introductionmentioning
confidence: 99%